Understanding management control systems in a traditional clannish society: an interpretive case study in Somalia - Hared, Bashir Abdisamad; Abdullah, Zarifah (IISTE, 2017)
Purpose- The main purpose of the paper is to understand and report the nature of management control systems (MCS) that is designed and used by the business organizations in the traditional clannish society of Somalia. Design/methodology/approach- A qualitative case study of a telecommunication company was adopted to gather both primary and secondary data. Semi-structured interviews were carried out with the executive directors of the main divisions. To triangulate the data sources, observations and document analysis were also used. Findings- The findings of the study reveal that the MCS of the case organization is extremely affected by the traditional norms of the Somali clannish environment.Although, the company practices some formal MCS techniques; i.e. budgeting and performance evaluation, compensation management and financial reporting, however, the role of the traditional clanism is visible in all aspects of the company’s daily operations. Hence, the main patterns of MCS include: clannish ownership, selective staffing and investors, collective responsibility of the clan/sub-clan members, personal trust and friendship, horizontal relationships and verbal communication. These control patterns have rendered the formal MCS techniques to become less relevant. Originality/value- The paper adds to the literature of MCS in the traditional societies especially in the African social context. Furthermore, the paper offers an insight to the academicians and practitioners about the business practices in the African traditional environments. Finally, the results of the study call for further researches, particularly in the traditional social settings that are mostly found in the less developed countries.